A case report of tardive subcutaneous emphysema in relation to iatrogenic pneumothorax - Christine Helene Opedal Ringvold; Ulla Møller Weinreich (SAGE Open Medical Case Reports, 2019)
Subcutaneous emphysema, the presence of air under the subcutaneous tissues, often arises in relation to pneumothorax, including iatrogenic pneumothorax. It can arise as a consequence of chest drain insertion and removal. This case report describes worsening of subcutaneous emphysema subsequent to chest drain removal, leading to tardive and life-threatening subcutaneous emphysema. There are few international guidelines describing chest drain removal and there are few reports describing tardive subcutaneous emphysema. These areas need further exploration using evidence-based research in order to develop a consensus on treatment options.